2022
DOI: 10.1039/d2sm00553k
|View full text |Cite
|
Sign up to set email alerts
|

Langevin dynamics simulation on optimal conditions for large and stable loops of adsorbed homopolymers on substrates

Abstract: Adsorption of polymer chains on solid surface is a universal interfacial behavior. Loops in the adsorbed chains are considered to exert significant effect on the overall properties of substrate-supported polymer...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Previous simulations based on similar polymer models showed that the critical attraction strength ε ps / k B T is about 1.0 for the adsorption of a single flexible polymer chain on a flat substrate. In this work, the smallest value of ε ps = 2 can provide a sufficient attraction for the polymer chains.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Previous simulations based on similar polymer models showed that the critical attraction strength ε ps / k B T is about 1.0 for the adsorption of a single flexible polymer chain on a flat substrate. In this work, the smallest value of ε ps = 2 can provide a sufficient attraction for the polymer chains.…”
Section: Resultsmentioning
confidence: 54%
“…The adsorbed layer, therefore, consists of two different chain structures: a high-density inner region composed of trains and a low-density outside region composed of loops and tails . Since the number of adsorbed polymer chains, denoted as ⟨ n ads ⟩, increases with increasing the substrate area, we use the “adsorbed amount,” denoted as Γ, to represent the total mass of monomers that belong to the adsorbed polymer chains per unit of the substrate area. , As the mass of every monomer is set as 1, we have normalΓ = n a d s N S with S = L x L y being the area of the substrate. Another physical variable to describe the adsorbed amount is the thickness, h ads .…”
Section: Resultsmentioning
confidence: 99%